Physical Activity is Associated with Health Related Quality of Life in Lymphoma Survivors Regardless of Body Mass Index; Results from the Profiles Registry. (2nd January 2022) - Vlooswijk, Carla; Oerlemans, Simone; Ezendam, Nicole P. M.; Schep, Goof; Slot, Stefanie; Thong, Melissa S. Y.; Vissers, Pauline A. J.; Beijer, Sandra
Abstract: Background: Being obese and having a sedentary lifestyle is associated with impaired health-related quality of life (HRQoL) among cancer survivors. The aim of the present study is to investigate the combined influence of body mass index (BMI) and physical activity on HRQoL in lymphoma survivors. Methods: Lymphoma survivors diagnosed between 1999 and 2012 were invited to complete questionnaires about body height and weight, physical activity and HRQoL using the EORTC QLQ-C30. Multivariable analyses were conducted to evaluate the association of BMI and physical activity on HRQoL. Results: 1.339 lymphoma survivors responded (response rate of 72%) of whom 43% had a healthy weight, 41% were overweight and 14% were obese. They spent on average 10 h, on moderate to vigorous physical activity (MVPA) per week. Multivariable linear regression analysis shows that relatively high active survivors reported higher HRQoL scores and less fatigue compared to relatively low active lymphoma survivors, regardless of BMI. Conclusion: MVPA was associated with higher HRQoL in lymphoma survivors regardless of BMI. Further studies, are needed to investigate effects of healthy lifestyle changes to improve HRQoL in lymphoma survivors. Research in understanding association of lifestyle factors may guide future support for lymphoma cancer survivors.